A morphometric analysis of the pathoanatomy of cervical spondylotic myelopathy and the correlation between magnetic resonance imaging findings and clinical presentation of patients - Zakaria@Mohamad, Zamzuri; Sharifudin, Mohd Ariff; Din, Hishamudin; Abdul Aziz, Azian (2016)
Background: Cervical spondylotic myelopathy (CSM) is the commonest cause of spinal cord dysfunction and MRI remains the imaging of choice for CSM. However, its findings are not completely specific for clinically significant CSM.